NANOPARTÍCULAS DE ALBUMINA BOVINA REVESTIDAS COM POLISORBATO 80 COMO CARREADORAS DE ANFOTERICINA B: DESENVOLVIMENTO TECNOLÓGICO E AVALIAÇÃO IN VITRO DA TOXICIDADE E DA EFICÁCIA - PEDROSO, LÍGIA SANTOS (2018)
Bovine serum albumin (BSA) nanoparticles coated with polysorbate-80 (PS-80) containing amphotericin B (AmB) were prepared by coacervation. The nanoparticles presented a uniform size distribution (0.241 ± 0.06), reduced size (185 ± 5 nm), high zeta potential (-38.0 ± 0.7 mV), suitable PS-80 adsorption (0,75 ± 0,04%) and great entrapment efficiency (93 ± 1%). The release profile of AmB was diffusion-controlled and showed low molecular aggregation in buffer solution. The physicochemical characteristic of AmB after synthesis were evaluated by X-ray diffraction (XRD), Fourier transformed infrared spectroscopy (FTIR), differential scanning calorimetry (DSC) and thermogravimetry (TG). Analysis in vitro of BSA-PS80/AmB NP demonstrated no citotoxicity over erythrocytes and effective activity antifungal against Cryptococcus neoformans ATCC 14116. Therefore, these nanosystems have potential for targeting AmB against Cryptococcus neoformans systemic infections in central nervous system.